ANALYSIS OF FACTORS THAT BACKGROUND ACEH WOMEN USING HIJAB - Rina Rahmi (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2019)
Abstract: This research is motivated by the results of observations and experiences of researchers, that found the majority of Acehnese women who are Muslim from the age range of ten years and above have used the veil. This study aims to analyze the factors underlying the veiled Acehnese women. The approach used is descriptive qualitative case study method. The data collection techniques used are direct observation, documentation, and interviews. Data sources for which the data used in this study are primary and secondary data sources. The data analysis technique used is the analysis of the structure of events where the researcher describes the events that occur. The results of this study are found to be the two factors underlying Acehnese women using the veil, namely Internal factors, and external factors. Internal factors consist of parental support and self-awareness. External factors consist of the environment (social culture) that drives it to use the veil and local government regulations contained in Aceh Qanun Number 11 of 2002 concerning the implementation of Islamic law in the fields of aqeedah, worship, and Islamic symbols. The hijab is included in the category of Islamic symbols. Regarding this, Islamic law requires all women to cover their aurat by wearing headscarves based on the laws contained in the Holy Qur’an and Hadith. According to most scholars the female aurat consists of the whole body except the hands and face.